2004
DOI: 10.1161/01.cir.0000139845.40818.75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isthmus Anatomy and Ablation Catheter on Radiofrequency Catheter Ablation of the Cavotricuspid Isthmus

Abstract: Background-Cavotricuspid isthmus (CTI) characteristics are rarely documented when comparing catheters in radiofrequency ablation (RFA) of atrial flutter (AFL). Our objectives were (1) to evaluate the impact of CTI morphology and length on ablation procedures and (2) to compare the efficacy of an 8-mm-tip catheter with an irrigated cooled-tip RFA in the subgroup presumed to be more difficult to treat (with a long CTI, Ͼ35 mm). Methods and Results-Over a period of 17 months, 185 patients accepted the protocol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 28 publications
4
73
1
Order By: Relevance
“…Although bidirectional conduction block across the isthmus effectively eliminates symptoms in a large majority of patients, 1,2 rare treatment failures are often ascribed to discontinuity in the ablation line 3 . A purely anatomically delivered contiguous line of lesions across the isthmus can be challenging to create, resulting in long procedural and ablation times 4–12 . Pathology studies have shown the CTI, in most cases, to be composed of discrete bundles of muscle with intervening connective tissue, 13 suggesting that a contiguous line of ablation may not be necessary to achieve bidirectional conduction block.…”
Section: Introductionmentioning
confidence: 99%
“…Although bidirectional conduction block across the isthmus effectively eliminates symptoms in a large majority of patients, 1,2 rare treatment failures are often ascribed to discontinuity in the ablation line 3 . A purely anatomically delivered contiguous line of lesions across the isthmus can be challenging to create, resulting in long procedural and ablation times 4–12 . Pathology studies have shown the CTI, in most cases, to be composed of discrete bundles of muscle with intervening connective tissue, 13 suggesting that a contiguous line of ablation may not be necessary to achieve bidirectional conduction block.…”
Section: Introductionmentioning
confidence: 99%
“…We could not achieve complete CTI bidirectional block in 16% of patients, which is the failure rate usually reported when using standard techniques (0–25% [3, 15,17,18,19, 22,34,35,36,37,38,39,40]). Excessive CTI thickness, existing pouches, recesses or trabeculations, local edema, or catheter instability during AF, are the suspected causes of failure.…”
Section: Discussionmentioning
confidence: 71%
“…Undoubtedly, collateral functional conduction block exists adjacent to the zone of thermal necrosis and no current diagnostic technology including most sophisticated imaging or recording techniques is capable of distinguishing between irreversible thermal damage and transient stunning of the tissue. Common atrial flutter ablation typically requires series of high‐power RF deliveries including cooled ablation in order to destroy sometimes bulky or anatomically complex CTI 14–16 . In the case of cooled‐tip technology, the situation may paradoxically complicate even more.…”
Section: Discussionmentioning
confidence: 99%